PENGARUH KOMPENSASI DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR KEMENTERIAN AGAMA KABUPATEN SOPPENG - Amaliyah, Hasni; Sahabuddin, Romansyah; Burhanuddin, Burhanuddin; Kurniawan, Agung Widhi; Ruma, Zainal (Jurnal Manajemen, 2023)
This study aims to determine how the effect of compensation and work motivation on employee performance. The number of samples used were 38 employees. Data collection was carried out using interviews, observations and questionnaires. The data analysis technique used is multiple linear regression analysis using the Statistical Product and Service Solution (SPSS). The results of this study indicate that the quality of compensation (X1) partially has a positive and significant influence on employee performance. Motivation (X2) partially has a positive and insignificant effect on employee performance. And simultaneously the two independent variables have a significant influence on employee performance.